Laporan Kasus: Kasus KDRT pada Anak - Mulyadi, Alfiana; Ahdi, Ainun Amalia; Novitasari, Novitasari; Mansyur, Mauluddin; Mathius, Denny; Assegaf, S. Zulfikar (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Domestic violence (DV) is a human rights violation with potentially severe consequences, particularly for children. This article presents a case report of a 10-year-old girl who suffered physical and psychological abuse by her stepmother. The study employed a qualitative case study method with in-depth interviews. Findings revealed that the child sustained multiple burn injuries and psychological trauma due to repeated abuse. Child abuse impacts not only physical health but also disrupts the child’s mental, emotional, and social development. This study highlights the urgent need for early intervention, legal protection, and the termination of domestic violence cycles to safeguard children’s rights and their future well-being.